2010
DOI: 10.1007/s10792-010-9411-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser photocoagulation (810 nm diode) for threshold retinopathy of prematurity: a prospective randomized pilot study of treatment to ridge and avascular retina versus avascular retina alone

Abstract: The purpose of this study was to compare the structural outcome of laser treatment to avascular retina and ridge versus laser treatment to avascular retina alone in cases with threshold retinopathy of prematurity (ROP). A prospective, randomized, interventional, comparative study of consecutive cases referred to a single tertiary center was considered here. 50 infants with bilateral symmetrical threshold ROP were recruited into this study over a period of 3 years. Threshold ROP was defined as per CRYO-ROP stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…3 Conventional laser photocoagulation can reduce the overproduction of VEGF in the retina and induce the regression of new vessels by ablating peripheral retina ischemic areas. 4,5 The BEAT-ROP (Bevacizumab Eliminates the Angiogenic Threat of Retinopathy of Prematurity) study 6 showed improved outcomes with intravitreal injection of bevacizumab (IVB) compared with conventional laser photocoagulation for Zone I ROP. However, more recently Sato et al 7 showed that bevacizumab escapes from the vitreous into the general circulation and could reduce systemic VEGF levels after IVB in premature infants, whereas Carneiro et al 8 have proved that ranibizumab does not alter systemic VEGF levels in adults.…”
mentioning
confidence: 99%
“…3 Conventional laser photocoagulation can reduce the overproduction of VEGF in the retina and induce the regression of new vessels by ablating peripheral retina ischemic areas. 4,5 The BEAT-ROP (Bevacizumab Eliminates the Angiogenic Threat of Retinopathy of Prematurity) study 6 showed improved outcomes with intravitreal injection of bevacizumab (IVB) compared with conventional laser photocoagulation for Zone I ROP. However, more recently Sato et al 7 showed that bevacizumab escapes from the vitreous into the general circulation and could reduce systemic VEGF levels after IVB in premature infants, whereas Carneiro et al 8 have proved that ranibizumab does not alter systemic VEGF levels in adults.…”
mentioning
confidence: 99%
“…When comparing the methods of single spots and near confluent photocoagulation, the method of dense laser photocoagulation seems to be more effective and safer [23][24][25] . The complications of the CALCR procedure do not vary in principle from the complications that are described in standard methods of treatment with laser and cryocoagulation under the visual control of an indirect ophthalmoscope [12][13][14][15][16]19,20,22 . In particular, we encountered a various extent of retinal and vitreous haemorrhages in all infants in our study group.…”
Section: Discussionmentioning
confidence: 98%
“…There are different views on the direct treatment of the ridge between the vascular and avascular parts of the retina 8,12,[12][13][14][15][16][17][18][19][20] . Near confluent laser photocoagulation, which was used in the CALCR procedure, seems to be more effective than the usage of individual laser spots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In severe forms of disease not responding to this laser photocoagulation further laser to the ridge as well as posterior to ridge has also been shown to be effective in severe cases of ROP. 10 This has caused regression of the disease in some cases and avoided the progression of tractional retinal detachment.…”
Section: Treatment Guidelinesmentioning
confidence: 99%